Mobile task management tool that improves workflow of an acute general surgical service. Issue 10 (2nd February 2015) - Foo, Elizabeth; McDonald, Rod; Savage, Earle; Floyd, Richard; Butler, Anthony; Rumball‐Smith, Alistair; Connor, Saxon
Abstract Background Understanding and being able to measure constraints within a health system is crucial if outcomes are to be improved. Current systems lack the ability to capture decision making with regard to tasks performed within a patient journey. The aim of this study was to assess the impact of a mobile task management tool on clinical workflow within an acute general surgical service by analysing data capture and usability of the application tool. Methods The Cortex iOS application was developed to digitize patient flow and provide real‐time visibility over clinical decision making and task performance. Study outcomes measured were workflow data capture for patient and staff events. Usability was assessed using an electronic survey. Results There were 449 unique patient journeys tracked with a total of 3072 patient events recorded. The results repository was accessed 7792 times. The participants reported that the application sped up decision making, reduced redundancy of work and improved team communication. The mode of the estimated time the application saved participants was 5–9 min/h of work. Of the 14 respondents, nine discarded their analogue methods of tracking tasks by the end of the study period. Conclusion The introduction of a mobile task management system improved the working efficiency of junior clinical staff. The application allowed capture of data not previously available to hospital systems. In the future, such data will contribute to the accurate mapping of patient journeys through the health system.